Tinjauan Atas Prosedur Sistem Kredit Kepemilikan Rumah Pada Kantor Pusat Developer Property Syariah Bogor - Amanda, Tasya; Sukartaatmadja, Iswandi; Sumantri, Samuel (Jurnal Aplikasi Bisnis Kesatuan, 2022)
The needs of human life are divided into three principles, namely clothing, food and shelter. The rapid growth rate has caused the need for clothing, food, housing to increase, especially in meeting primary needs such as housing, so there is a mortgage system that helps residents to obtain basic/primary housing needs. This study aims to determine the financing model or procedure used by the Sharia Property Developer Head Office in providing Non-Bank Sharia Home Ownership Loans to the public. Non-bank Sharia Home Ownership Loans are basically home loans for prospective home buyers who do not use banks in practice. The results showed that the financing model for non-bank Sharia Home Ownership Loans was not the same as Sharia Ownership Loans that used banks. The results of this study are that Sharia Home Ownership Credit at Sharia Property Developers uses the concept of bankless credit, without fines, free of usury, without confiscation and without problematic contracts, so that sharia mortgages at Sharia Property Developers are in accordance with the principles of sharia mortgages in Islam. Keywords: Review of Food Needs, Sharia Home Ownership Loans, Sharia Property Developers